1997
DOI: 10.1007/s002940050187
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of a gene encoding protein disulphide isomerase, pdiA, from Aspergillus niger

Abstract: Current strategies to improve the secretion of heterologous proteins from Aspergillus niger include the manipulation of chaperones and foldases specific to the endoplasmic reticulum (ER). Here we report the isolation of a gene, pdiA, encoding a putative protein disulphide isomerase (PDI) from A. niger using the Saccharomyces cerevisiae PDI gene as a probe. Sequencing of a genomic clone and RT-PCR products predict a 515-aa protein comprising a 20-aa ER-translocation signal sequence and a 495-aa mature protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…Expression profiles of non-Aspergillus species suggested by BLAST matches may be unreliable (43). Two of these genes, the ER chaperone bipA and protein disulfide isomerase pdiA, have been previously shown to be up-regulated during recombinant protein secretion (29,36,52). The unknown genes that were up-regulated included some with BLAST hits to secretion-related genes including chaperones, heat shock proteins, and GTP-binding proteins from other species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression profiles of non-Aspergillus species suggested by BLAST matches may be unreliable (43). Two of these genes, the ER chaperone bipA and protein disulfide isomerase pdiA, have been previously shown to be up-regulated during recombinant protein secretion (29,36,52). The unknown genes that were up-regulated included some with BLAST hits to secretion-related genes including chaperones, heat shock proteins, and GTP-binding proteins from other species.…”
Section: Resultsmentioning
confidence: 99%
“…Some improvements in recombinant protein production have been seen from overexpressing chaperones and foldases in yeast (18,19). However, the overexpression of equivalent proteins in aspergilli has had variable effects: some constructs showed increased intracellular recombinant protein production but no increase in extracellular levels, while others showed no improvement at all (27,29,36). The conflicting evidence surrounding overexpression of secretion-related genes emphasizes the complexities of protein-folding interactions, the specific effects of different products, and the possible need for a coordinated increase in expression to optimal levels (27).…”
mentioning
confidence: 99%
“…The expression of chaperone-and foldase-encoding genes is induced by situations of stress in the ER that result in the accumulation of unfolded proteins through the so-called unfolded protein response (UPR) pathway (for reviews, see references 7 and 49). In filamentous fungi, UPR-inducing agents have been shown to provoke a rapid and strong increase in the expression of the major ER-resident chaperone binding protein (BiP) (28,43), whereas induction of the expression of foldases of the protein disulfide isomerase (PDI) family occurred in a delayed and/or less intense fashion (27,28,37).…”
mentioning
confidence: 99%
“…Accumulation of unfolded proteins in the endoplasmic reticulum is known to activate the UPR, in both lower and higher eukaryotes. In filamentous fungi, UPR induction has been reported to take place under conditions in which protein transport or folding is impaired by treatment of the cultures with different chemical agents or under conditions where a heterologous protein is produced (Mulder et al, 2004;Ngiam et al, 1997;Pakula et al, 2003;Punt et al, 1998;Saloheimo et al, 1999Saloheimo et al, , 2003van Gemeren et al, 1997). In addition, we have recently shown that the UPR pathway is activated along with cellulase gene induction when the cultures are shifted from a glucose repressed state to an induced state (CollĂ©n et al, 2004).…”
mentioning
confidence: 99%